Serving 'the Cause': Cecil Jackson-Cole and the professionalization of charity in post-war Britain. Issue 260 (1st April 2020) - Field, Jessica
Abstract: This article explores the relationship between faith, business and charity in mid to late twentieth-century Britain by examining the work of Cecil Jackson-Cole, co-founder of Oxfam, founder of Help the Aged, ActionAid and many other charities. Jackson-Cole's approach to 'building-up' a charity accelerated the ongoing professionalization of the sector. This did not, however, represent a complete break from the Christian charity ethos of the past. By examining Jackson-Cole's faith and its influence on his charity business network and practices, it is possible to see an enduring symbiotic relationship between faith and professionalization in organized charity across the twentieth century.